2016
DOI: 10.3389/fpls.2016.00213
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Genetic Diversity and Phenotypic Plasticity in Determining Invasion Success of a Clonal Weed in the USA and China

Abstract: Phenotypic plasticity has been proposed as an important adaptive strategy for clonal plants in heterogeneous habitats. Increased phenotypic plasticity can be especially beneficial for invasive clonal plants, allowing them to colonize new environments even when genetic diversity is low. However, the relative importance of genetic diversity and phenotypic plasticity for invasion success remains largely unknown. Here, we performed molecular marker analyses and a common garden experiment to investigate the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 65 publications
3
96
1
1
Order By: Relevance
“…Stem fragments of plants of A. philoxeroides were collected from five locations in the United States (introduced range) and five locations in Argentina (native range) in 2005 and 2006, respectively (Table ; Figure ). In a previous study, we found that each of the sampled plants was characterized by a unique multilocus genotype (Geng et al, ). The sampled genotypes were transplanted in a greenhouse and vegetatively propagated three times to remove potential differences due to environmental maternal carry‐over effects (Schwaegerle, McIntyre, & Swingley, ).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Stem fragments of plants of A. philoxeroides were collected from five locations in the United States (introduced range) and five locations in Argentina (native range) in 2005 and 2006, respectively (Table ; Figure ). In a previous study, we found that each of the sampled plants was characterized by a unique multilocus genotype (Geng et al, ). The sampled genotypes were transplanted in a greenhouse and vegetatively propagated three times to remove potential differences due to environmental maternal carry‐over effects (Schwaegerle, McIntyre, & Swingley, ).…”
Section: Methodsmentioning
confidence: 92%
“…S1; Figure S2). In a previous study, we found that each of the sampled plants was characterized by a unique multilocus genotype (Geng et al, 2016). The sampled genotypes were transplanted in a greenhouse and vegetatively propagated three times to remove potential differences due to environmental maternal carry-over effects (Schwaegerle, McIntyre, & Swingley, 2000).…”
Section: Study Speciesmentioning
confidence: 99%
“…) and may be critical in range expansion (Geng et al . ). It may have initially aided adaptation into the secondary invasion areas.…”
Section: Discussionmentioning
confidence: 97%
“…; Geng et al . ) could also reduce fitness. Phenotypic plasticity is considered to be a trait that is potentially beneficial across habitats (Nicotra et al .…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic plasticity is considered as one of the underlying mechanisms of general purpose genotype (GPG) model (Massicotte and Angers 2012) and is more important in rapidly fluctuating habitats (Clements and Ditommaso 2011). Many studies have highlighted the role of phenotypic plasticity on the successful invasion of exotic plant species (Hagenblad et al 2015;van Kleunen et al 2010), mostly for clonal species for which local adaptation is usually not observed (Geng et al 2016). Clones of an invasive species Alternanthera philoxeroides showed varying levels of genetic diversity (in terms of both ISSR marker diversity and quantitative trait variation) between and within its native range (Argentina) and two invasive ranges -China and the USA (Geng et al 2016).…”
Section: Genetic Adaptation Paradox and Epigenetic Regulation Of Phenmentioning
confidence: 99%